Hukum Perkawinan dalam Masyarakat Hukum Adat Indonesia - Ridho Oktavian; Dzulkifli Hanafi; Maulana Ramdani; Faturohman Faturohman; Humaeroh Humaeroh (International Forum of Researchers and Lecturers, 2026)
Marriage in Indonesian customary law communities is a social institution that not only binds individuals but also involves families and the wider community, encompassing legal, cultural, and spiritual dimensions. Within this diversity, issues arise regarding the alignment between customary law and national law. The major research problem concerns the forms, requirements, and procedures of marriage in customary law communities, while the minor problem focuses on the dynamics between customary law and national law in terms of validation and legal protection. This study is situated within the general context of customary law communities in Indonesia. The objective is to comprehensively examine customary marriage law and its implications for the national legal system. The research applies statutory and conceptual approaches within a normative legal research framework, using a descriptive-analytical method supported by library research and qualitative analysis. The findings indicate that customary marriage law is diverse, including forms such as bridewealth marriage, semenda, independent marriage, and elopement, all influenced by kinship systems. Furthermore, there is a dualism between customary recognition and state legality, making marriage registration essential to ensure legal certainty.